MENINGKATKAN PRESTASI BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA KELAS VI SD NEGERI 020 TEMBILAHAN HILIR - St. Hadijah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The study aims to explain the effect of Jigsaw type cooperative learning on the IPS learning outcomes and howfar the comprehension and mastery of IPS subjects after the implementation of Jigsaw type cooperative learningon the students of class VI of SD Negeri 020 Tembilahan Hilir. This research activity was conducted at SDNegeri 020 Tembilahan Hilir. This research was conducted in October odd semester of academic year2016/2017 with subject of 20 students. The study was conducted in two cycles with qualitative descriptivetechnique. The results of the action analysis show that: First, Jigsaw type cooperative learning has a positiveimpact in improving students 'learning achievement marked by the improvement of students' learning mastery inevery cycle, that is cycle I (60.00%) and cycle II (90.00%). Second, the application of cooperative learning typeJigsaw has a positive influence, which can improve students' learning motivation in IPS learning, it is shown byenthusiastic students who stated that students are interested and interested in cooperative learning type Jigsawso they become motivated to learn. Third, Jigsaw type cooperative learning has a positive impact on cooperationamong students, it is shown that there is a responsibility in groups where students are better able to teach theirless fortunate friends.